Staff-Family Partnership and Teamwork Skills as Predictors of Sense of Community in Public Schools - Espirituoso, Ciela Anne; Carreon, Hazel (Journal of Interdisciplinary Perspectives, 2025)
The sense of community in public schools is a vital component for fostering a supportive and inclusive environment for students, teachers, and families. This study investigated whether staff-family partnership and teamwork skills predict sense of community in public schools. A quantitative method was used in the survey with 300 senior high students from grades 11 to 12 in a large public secondary school within the Division of Davao Oriental, specifically Cateel 1 and 2 District, as respondents. Results showed that the level of staff-family partnership is often manifested, as are teamwork skills and a sense of community. These findings highlight a strong sense of belonging among school members. Notably, the relationships between staff-family partnership and sense of community, as well as teamwork skills and sense of community, were found to be significant. On the other hand, both staff-family partnership and teamwork skills could significantly predict the sense of community. In addition, among the predictors, leadership had the highest standardized beta, suggesting that it has the most decisive influence on sense of community. Also, 72.4% of the variation of sense of community could be attributed to the combined impact of the variables being investigated. Therefore, it is recommended that efforts should be made to improve professional care by providing professional development programs, strengthening communication through regular student-staff-family dialogues, and prioritizing leadership development by providing leadership training.